Polymer-buried van der Waals magnets for promising wearable room-temperature spintronics - Hu, Liang; Zhou, Jian; Hou, Zhipeng; Su, Weitao; Yang, Bingzhang; Li, Lingwei; Yan, Mi (Materials horizons, 2021)
The demand for high-performance spintronic devices has boosted intense research on the manipulation of magnetism in van der Waals (vdW) magnets. Despite great efforts, robust ferromagnetic transitions above room temperature still face significant hurdles. Strain engineering can reversibly regulate magnetic exchange, but the degree of regulation is still impractical for most magnetic applications. Hereby we employ a large-strain transferrer to produce tunable strains of up to 4.7%, which induces authentic room-temperature ferromagnetism in large-area Fe 3 GeTe 2 nanoflakes with 20-fold improvement in magnetization. The record increment of the Curie temperature ( T C ) of well above 400 K originates from the strain-enhanced magnetic anisotropy and excellent magnetoelastic coupling. The correlation between the emerging ferromagnetism and Raman spectral evolution is also established, which complements well the T C phase diagram in a large-strain region. In addition, an unusual exchange bias effect with a vertical magnetization shift is tracked for the first time upon bending, which reveals the hidden competition between antiferromagnetic and ferromagnetic coupling. The reversible strain manipulation of single-domain ferromagnetic order in a single nanoflake further opens up a route to develop low-power wearable spintronic devices. The findings here provide vast opportunities to exploit the possibility of practical applications of more vdW magnets. A record Curie temperature of well above 400 K is reversibly realized in large-tensile strain-coupled van der Waals Fe 3 GeTe 2 nanoflakes.